Comparison of CO2, N2, CO, H2S, CH4, and H2O adsorptions onto sI methane hydrate surface - Zhang, Ming; Zhao, Baoli; Li, Jiahua; Li, Tiantai; Li, Jian (Frontiers in Earth Science, 2022)
By employing molecular dynamic (MD) and density functional theory (DFT) calculations, the adsorptions of CO2, N2, CO, H2S, CH4, and H2O onto methane hydrate (MH) surface are compared in this work. The methane hydrate planes of (001) and (110) and various cleaving sites are compared with cleavage energies. MH(001) has more tendency to form when compared with MH(110) in thermodynamics. Two different terminations of MH(001) surfaces are compared, and MH(001)-I (terminated with CH4+H2O) leads to more negative adsorption energies when compared with MH(001)-II (terminated with H2O only). The priority sequence of the adsorptions can be queued as: H2O > H2S > CO2 > N2 > CH4 > CO. Namely, CO2, N2, and H2S have potential to replace CH4 in methane hydrate. The interfacial hydrogen bond and electronic interactions are clarified for the adsorptions of CO2, N2, and H2S. The hydrogen bonds tend to form between O-H atom pairs of CO2-H2O, N-H atom pairs of N2-H2O, and S-H and H-O atom pairs of H2S-H2O, respectively. The bonds are mainly contributed from the dispersion interaction between the O-2p in CO2 and H-1s in H2O, N-2p in N2 and H-1s in H2O, S-3p in H2S and H-1s in H2O, and H-1s in H2S and O-2p in H2O, respectively.